(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
One of the most admired characteristics of bird behavior is song but there are many examples of discrimination of aesthetic stimuli by animals. A wide range of animals, from fish to primates, successfully learn discrimination of music, while preference for particular music is rather rare in animals, although songbirds prefer some musical stimuli to others. Some animals, such as chimpanzees and elephants, draw and paint, however the animals do not “enjoy” their products and the products do not have a reinforcing property to other conspecifics. This constitutes the clear difference between human art and the art-like behavior of animals.